18f-20f+18=-4f-10

Simple and best practice solution for 18f-20f+18=-4f-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18f-20f+18=-4f-10 equation:



18f-20f+18=-4f-10
We move all terms to the left:
18f-20f+18-(-4f-10)=0
We add all the numbers together, and all the variables
-2f-(-4f-10)+18=0
We get rid of parentheses
-2f+4f+10+18=0
We add all the numbers together, and all the variables
2f+28=0
We move all terms containing f to the left, all other terms to the right
2f=-28
f=-28/2
f=-14

See similar equations:

| (x-25)(x+24)=600 | | (x-25)(x+13)=325 | | 1=-1+t6 | | 19x=-12x | | 25=-2r+3 | | -9.1d+10.8=6.02-2.2d+19.96 | | 9=3(q+8) | | -h-18=18+4+4h | | -6q-1+7q=2q+14 | | 4=2/3(r-6) | | 3x+7x=-70 | | 8+14b-b=12b-8 | | 7(b+3)+5(b+9)=1 | | 7q+16=44 | | -5x+x/7=-3 | | -17=n-7/3 | | -7(y+4)=-5y-3 | | 5(4z+5)=8z+1 | | v2+16=20 | | 7(3n+5)=7n+4 | | w+10/4=4 | | 8y+5(5y-6)=16 | | 9b+2(5b-5)=13 | | 6a+4(5a-7)=15 | | (n-1)^2=0 | | 14x+67=7x+50 | | w+104=4 | | x+x*0.2=890 | | -5(c+5)=-20 | | s/7-1=3 | | 56=t/5+46 | | 11=10+r2 |

Equations solver categories